Neoliberalism and the economic groups of Monterrey - Pérez-Sánchez, Beatriz (2023)
In its beginnings in Mexico, the renewal of liberalism manifested itself as support for the alternative project of economic nationalism adopted by the financial elite throughout the 20th century. However, economic nationalism was established as an ideology that supported the economic policy of the State. The objective of this study was to know the main theoretical characteristics and particularities of the neoliberal model that allowed the economic groups of the country and especially those of Monterrey to accumulate and reproduce capitalism successfully. The methodology corresponds to a documentary-type investigation that used historical-analytical methods, with a descriptive scope that was supported by secondary sources of information. The results indicate that the growth strategies, assets, corporate structure, alliances and financing of the economic groups of Monterrey supported by the neoliberal model place their role in the era of market globalization, consolidating the reproduction of capitalism.